Composites of plasma treated poly(etherimide) films with gold nanoparticles and lysine through layer by layer assembly: a ``friendly-rough'' surface for cell adhesion and proliferation for tissue engineering applications - D'Britto, Virginia; Tiwari, S.; Purohit, V.; Wadgaonkar, P. P.; Bhoraskar, S. V.; Bhonde, Ramesh R.; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2009)
A composite film fabricated by plasma treated poly(etherimide) with subsequent deposition of gold nanoparticles and lysine using layer by layer assembly has been demonstrated to be good for cell attachment and proliferation making it an attractive strategy for tissue engineering applications. As compared to the other methods the decrease in contact angle obtained here does not depend much on the plasma treatment thus affecting the polymer structure minimally. A combination of surface roughness provided by the gold nanoparticles and the presence of amine groups of lysine is hypothesized to be the reason for the features observed.